Modeling temperature distribution in the driving elements INTEGRATED CIRCUITS RESULTING electrostatic discharge - G. A. Piskun; V. F. Alexeev; V. L. Lanin; V. G. Levin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Investigated experimentally the principle of propagation of thermal fields in integrated circuits as a result of electrostatic discharge. A numerical model of the temperature distribution in the current-carrying elements of integrated circuits due to contact effects of static electricity, and electrical conductivity based on the Fourier analysis of the thermal conductivity is proposed. The developed model predicts the temperature dependence of the discharge voltage and identify the most vulnerable conductive region by identifying local areas of melting.